Pharmacokinetics and toxicokinetics of d-serine in rats - Hasegawa, Hiroshi; Masuda, Nami; Natori, Hiromi; Shinohara, Yoshihiko; Ichida, Kimiyoshi (Journal of pharmaceutical and biomedical analysis, 2019)
•We investigated the relationship of d-serine kinetics with nephrotoxicity in rats.•Following iv/po/ip d-serine, we measured plasma d-/l-serine with GC–MS.•Histology revealed renal damage 24 after ip administration of d-serine at doses of 1.8–4.8 mmol/kg bw.•When Cmax of d-serine was >2 μmol/ml, plasma creatinine increased 24 h later.•Thus, Cmax of d-serine could be a good predictor of d-serine-induced nephrotoxicity. In the mammalian brain, d-serine acts as a co-agonist at the glycine-binding site on the N-methyl-d-aspartate receptor. Because plasma d-serine levels are significantly lower in patients with schizophrenia than in healthy subjects, d-serine has been proposed as a potential therapeutic agent for schizophrenia treatment. However, d-serine has a nephrotoxic effect in rats at high doses. The purpose of this study was to investigate the relationship between the plasma kinetics of d-serine and nephrotoxicity in rats. We administered d-serine intravenously (iv), orally (po), or intraperitoneally (ip) to male Wistar rats, and performed gas chromatography-mass spectrometry to measure the plasma concentrations of d- and l-serine. After iv administration (0.1 mmol/kg body weight (bw)), plasma d-serine declined multiexponentially with an elimination t1/2 of 108 ± 16 min, and the total clearance was 7.9 ± 0.9 ml/min/kg bw. The oral bioavailability of d-serine was estimated to be 94 ± 27%. To evaluate the dose–response relationship of d-serine-induced kidney injury and the plasma kinetics of d-serine, we injected d-serine into rats ip in doses ranging from 0.6 to 4.8 mmol/kg bw. Twenty-four hours after d-serine administration, histological changes indicating renal damage were observed in the kidneys of rats who received d-serine at doses of 1.8–4.8 mmol/kg bw; the severity of the tubular injury increased with increasing d-serine dose. When the Cmax value of d-serine was approximately >2 μmol/ml, the plasma creatinine increased remarkably 24 h after d-serine administration. This suggests that the Cmax of d-serine could be a good predictor of d-serine-induced nephrotoxicity.